The relationship between the L2 Motivational Self System and attainment - Sandeman, David (Lingua Posnaniensis, 2022)
Motivation is widely accepted to be a crucial aspect of language learning, and a variety of models of motivation have been proposed over the years. The L2 Motivational Self System is a particularly interesting model that reconceptualizes motivation as a function of possible future self-guides, and has far-reaching pedagogical implications. Critics have pointed out that there is little evidence connecting L2 Motivational Self System to attainment, as it is inconsistently correlated with L2 proficiency and is only a weak predictor of results. However, as this paper details, these criticisms ignore the correlation between the L2 Motivational Self System and other behaviors and attitudes associated with attainment, such as willingness to communicate, self-efficacy, persistent learning, and low L2 anxiety.